2016
DOI: 10.1128/aem.03111-15
|View full text |Cite
|
Sign up to set email alerts
|

A NewN-Acyl Homoserine Lactone Synthase in an Uncultured Symbiont of the Red Sea Sponge Theonella swinhoei

Abstract: i Sponges harbor a remarkable diversity of microbial symbionts in which signal molecules can accumulate and enable cell-cell communication, such as quorum sensing (QS). Bacteria capable of QS were isolated from marine sponges; however, an extremely small fraction of the sponge microbiome is amenable to cultivation. We took advantage of community genome assembly and binning to investigate the uncultured majority of sponge symbionts. We identified a complete N-acyl-homoserine lactone (AHL)-QS system (designated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…A recent culture‐independent study revealed a novel QS system associated with an uncultured Rhodobacteraceae bacterium, which was shown to represent approximately 3 % of the sponge microbiome. The LuxI homolog ( tswI ) was expressed heterologously, and was shown to produce some of the same signal molecules detected in the sponge tissue 20. Thus, AHL‐QS systems are present in sponges, and appear to be a common feature in Alphaproteobacteria of the Rhodobacterales order.…”
Section: Introductionmentioning
confidence: 99%
“…A recent culture‐independent study revealed a novel QS system associated with an uncultured Rhodobacteraceae bacterium, which was shown to represent approximately 3 % of the sponge microbiome. The LuxI homolog ( tswI ) was expressed heterologously, and was shown to produce some of the same signal molecules detected in the sponge tissue 20. Thus, AHL‐QS systems are present in sponges, and appear to be a common feature in Alphaproteobacteria of the Rhodobacterales order.…”
Section: Introductionmentioning
confidence: 99%
“…symbiont has been postulated to aid in attachment to the eukaryotic host and in avoidance of the host's immune response (Alex and Antunes, 2015). ANK-repeat proteins (ARPs) have been identified in abundance in the genomes of multiple sponge-associated bacteria (Liu et al, 2010;Thomas et al, 2010;Siegl et al, 2011;Fan et al, 2012;Hentschel et al, 2012;Tian et al, 2014;Alex and Antunes, 2015;Burgsdorf et al, 2015b;Britstein et al, 2016), including in the most dominant core symbiont of A. queenslandica, OTU 1, although not in OTU 4 (Gauthier et al, 2016). ARPs from bacterial symbionts have been experimentally shown to influence sponge-bacterial interactions, specifically via interfering with phagocytosis as a possible mechanism to escape digestion in a sponge host (Nguyen et al, 2014).…”
Section: Differential Expression Analysis Of Sponge Genes Indicates Smentioning
confidence: 99%
“…Single-cell genomic and metagenomics studies have contributed to correlating particular traits with specific symbiont lineages Siegl et al, 2011;Kamke et al, 2013;Gao et al, 2014;Tian et al, 2014;Wilson et al, 2014;Burgsdorf et al, 2015;Britstein et al, 2016), revealing functional gene convergence in phylogenetically-distinct microbial communities with core features that likely reflect adaptation of microorganisms to the sponge host environment Hentschel et al, 2012). Traits that have repeatedly been reported in prokaryote symbionts of poriferans include versatile nutrient utilization, protection from environmental and host-specific stress, and eukaryotic-like proteins Hentschel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%